Sosialisasi dan Penggalian Potensi Penerapan Ekonomi Sirkular dalam Upaya Meningkatkan Pendapatan Nelayan Bojong Salawe Kabupaten Pangandaran - Thirafi, Luthfi; Akbarsyah, Nora; Fauzan, Farisadri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Pangandaran Regency as a tourist area with a long coastline has enormous potential for marine tourism and fisheries. Unfortunately, this is followed by environmental pollution that occurs. Our program tries to offer the application of a circular economy to minimize this problem. This program uses a design thinking approach and involves fishermen from Bojong Salawe Village in counseling activities and discussions regarding the economic conditions of fishermen and the potential of natural resources that can be utilized for new sources of income. The results of the discussion provide information that fishermen in Bojong Salawe have economic problems during the lean season, so additional sources of income are needed other than fish catches. The application of the circular economy can be used to help fishermen increase their income given the fact that as many as 85% of fishermen are still in the productive age and as many as 53% of other fishermen still depend only on fish catches. In addition, information was obtained regarding the potential utilization of mangrove fruit of the type Rhizophora sp. to be reprocessed into a product to provide an opportunity for fishing families to earn new income.